Kinetics of the Leaching Process of an Australian Gibbsitic Bauxite by Hydrochloric Acid - Aichun Zhao; Ting-an Zhang; Guozhi Lv; Wenyan Tian (Advances in Materials Science and Engineering)
Gibbsitic bauxite from Australia was leached by hydrochloric acid in this work. Analysis on kinetics for the extraction of Al2O3 was quantitatively studied. It was concluded that the hydrochloric acid leaching process of gibbsitic bauxite was controlled by chemical reaction. Moreover, the mechanism for the dissolution followed the equation, ln⁡k=39.44-1.66×104(1/T), with an apparent activation energy of 137.90 kJ/mol, according to the equation of k=Ae-Ea/RT. This work aims to provide a good theory support for the process control by using a new method of alumina production from the low grade bauxite.